Surface modification on cocrmo alloy to improve the adhesion strength of hydroxyapatite coating - Mas Ayu Hassan (N/A, 2017)
Surface modification on cocrmo alloy to improve the adhesion strength of hydroxyapatite coating by Mas Ayu Hassan